The Effect of Digital Transformation on Bank Financial Performance with Fee Based Income as an Intervening Variable in Commercial Banks Listed on the IDX in the 2020-2023 Period - Hidayat, Taufiq; Anabel, Skolastika (STIE Indonesia Banking School, 2025)
Digital transformation has become a significant trend across all industrial sectors, aiming not only to address contemporary challenges but also to improve companies' operational performance. This study investigates the effect of digital transformation and fee-based income on the financial performance of banks. Specifically, it examines whether digital transformation significantly enhances financial performance (measured by ROA) through the mediation of fee-based income. The study adopts the latest digital transformation metrics developed in China and focuses on banking sector companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Secondary data were collected from financial and annual reports using purposive sampling, resulting in a final sample of 40 firms. The analysis was conducted using multiple linear regression with E-Views 12 software. The findings demonstrate that digital transformation and fee-based income both positively and significantly affect banks' financial performance, both jointly and individually. Furthermore, digital transformation is shown to have a significant positive impact on ROA through the mediation of fee-based income. Future research is recommended to include non-bank financial institutions as research subjects, incorporate additional variables, and assess financial performance over a longer period.